Hubungan Tingkat Dukungan Keluarga, Pengetahuan Keluarga dan Peran Kader Terhadap Kunjungan Balita Ke Posyandu Tahun 2023 - Mardiana, Ommy; Madjid, Syarah; Rumbawa, Imela; Idham, Jamila (Media of Health Research, 2024)
Indonesia still faces nutritional problems, one of which is undernutrition. Undernutrition is a nutritional issue that can affect toddlers. Toddlers, defined as children aged 0–59 months, need close monitoring of their growth and development since they are in the "Golden Age" phase. Toddlers experiencing undernutrition can be identified by their thin body condition, indicated by a weight-for-length or height score falling between -2 to -3 standard deviations, and/or an upper arm circumference of 11.5–12.5 cm in children aged 6–59 months. Research Objective: To determine the relationship between family knowledge, family support, and the role of health cadres in toddler visits to the integrated health post (Posyandu) at Harapan Raya Health Center. Research Contribution: While this study does not generate new theories, it is expected to contribute ideas within the field of public health. Additionally, it aims to provide researchers with insights and experience, broadening their knowledge, and serving as useful information for future studies.